Modelagem e imageamento sísmico da Bacia do Jequitinhonha - SOUZA, Igor de Jesus Sousa (2018)
The present work had aimed at an evaluation of the seismic modeling, processing and imaging of a line of the marine part of the Jequitinhonha Basin. In this sense, we emphasize the need for the physical, mathematical and computational understanding of the methods and processes involved. The modeling method was based on ray theory, which is directly related to the modeling and processing methods (NMO and CRS). The processing methods were the NMO and CRS in order to locate specular interfaces and diffraction zones, where the method with the best visual definition was accredited; thus, the CRS delineated better the reflectors in the CRS-stacked and CRS-migrated sections. An initial part of this study was the velocity model representation in the seismic domain, 𝑣(𝑡), and in the geological domain 𝑣(x). The distribution of velocities of the waves P, 𝑣𝑃 , (where can be added the so desired information of the S waves, 𝑣𝑆), is fundamental for the parts of the seismic processing and migration that looks for a geological interpretation. As a detail of a future modeling to be highlighted is of 3D structures Jequitinhonha Basin, aiming at numerical modeling of the basin, where is necessary the knowledge of the P and S velocities, and the density distribution in the subsurface. Usually this additional and detail knowledges are constructed by empirical models, that results in the possibility of going beyond the migration processes and realize the pressure prediction, deformation and stress distribution in the subsurface. The pressure variation defines zones of low and high pressure that behaves like natural pumping for the accumulation of fluids (oil, gas and water). In addition to the natural pumping process, it is required geological conditions such as oil and gas generation, thermal regime, and confined trapping.